Avoidance Interoceptive Disorder Treatment in Ankylosing Spondylitis - Fernando Gimeno Marco*; Isabel Castillo Salazar; Gabriel Domínguez Almuzara; Javier Tenas Gonzalvo; Susana Ara Gimeno; Cristina Hernández Jordán; Héctor Gutiérrez Pablo; Marta Pie Villacampa; Adrián Najarro López; Juan Carlos Carrión Pareja; Elena Charte Alegre (Global Journal of Medical and Clinical Case Reports, 2025)
Abstract In Ankylosing Spondylitis (AS), sub-axial cervical involvement associated with episodes of neck pain is often observed. The pain and the anticipation of physical damage in these episodes can trigger a conditioned anxiety response with panic attacks, resulting in an Interoceptive Avoidance Disorder (IAD). Using a multiple baseline n = 1 between-subjects design, in vivo exposure treatment was implemented using a joint mobility routine and cognitive-behavioral coping strategies in two cases of AD affected by IET. After 14 weeks, both cases were discharged. During treatment, the efficacy of the in vivo exposure technique used is verified. The possibility of application in other analogous cases, in which the characteristic symptoms of AD act as a trigger for the problem, and the contribution to the reduction of anxious symptoms, justifies the consideration of this treatment for the improvement of the state of health in the EA.